Comparison of Incidences of Intravascular Injection between Medial and Lateral Side Approaches during Traditional S1 Transforaminal Epidural Steroid Injection - Sang Jun Park; Shin Hyung Kim; Seon Ju Kim; Duck Mi Yoon; Kyung Bong Yoon (Pain Research and Management)
Purpose. Intravascular injection rates are higher during traditional S1 transforaminal epidural steroid injection (TFESI) compared with lumbar transforaminal injection. We compared the incidences of intravascular injection between the medial and lateral approaches to the S1 foramen during S1 TFESI. Materials and Methods. A total of 139 patients underwent one or more TFESIs (170 total injections). The patients received S1 TFESI by either medial or lateral side of S1 foramen under fluoroscopic anteroposterior view using digital subtraction method. The intravascular injection rates, epidural spread patterns, and contrast volumes required to reach the superior aspect of the L5-S1 intervertebral disc (SIVD) were compared between groups. Results. Intravascular injection rates during S1 TFESI were significantly lower in the medial approach compared with the lateral approach patients (4.9% versus 38.6%, resp., P<0.001). The medial approach group had more epidural spread to the L5-S1 SIVD than the lateral group (82.1% versus 58.8%, resp.); lower contrast volume amounts were required to extend the L5-S1 SIVD (1.46±0.48 versus 1.90±0.62, resp.). Conclusion. During S1 TFESI, approaching the needle towards the medial part of the S1 foramen may reduce intravascular injection risk.